Resource Orchestration Strategies To Promote Innovation And Sustainability In Tourism - Sofie Ratna Artanti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to explore the role of Resource Orchestration (RO) strategies in supporting innovation and sustainability in the tourism sector. The research employs a qualitative approach with a literature review, analyzing sources related to resource management, product development, and the social-environmental impacts of tourism. The findings suggest that RO strategies are vital in fostering collaboration between tourism companies, governments, and local communities to manage destinations sustainably. The application of digital technologies and community empowerment also contributes to improved operational efficiency and cultural preservation. The study concludes that RO can create a balance between innovation and sustainability, providing practical insights for developing long-term sustainable tourism strategies.